2022
DOI: 10.1029/2022jb024693
|View full text |Cite
|
Sign up to set email alerts
|

The 2020 Westmorland, California Earthquake Swarm as Aftershocks of a Slow Slip Event Sustained by Fluid Flow

Abstract: Earthquakes are often seen to cluster in time and space. Many clusters have a clearly identifiable mainshock followed by numerous smaller aftershocks. Others occur as a sustained burst of small magnitude earthquakes lasting from hours to several years without an obvious mainshock, referred to as a swarm (Mogi, 1963). The peak seismicity rate during swarms can reach >10,000 times the background level with complex temporal evolution that cannot be explained by the simple Omori-Utsu type power-law decay (Omori, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 199 publications
1
7
0
Order By: Relevance
“…Tectonic forcing, weakening of faults due to pore pressure changes, and event‐to‐event triggering due to stress perturbations imposed by single events can act simultaneously during a seismic swarm. Similar complex interactions of fluids, (aseismic) tectonic processes, and/or magmatic processes have been proposed in other studies of seismic swarms (e.g., Lanza et al., 2022; Legrand et al., 2011; Sirorattanakul et al., 2022).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Tectonic forcing, weakening of faults due to pore pressure changes, and event‐to‐event triggering due to stress perturbations imposed by single events can act simultaneously during a seismic swarm. Similar complex interactions of fluids, (aseismic) tectonic processes, and/or magmatic processes have been proposed in other studies of seismic swarms (e.g., Lanza et al., 2022; Legrand et al., 2011; Sirorattanakul et al., 2022).…”
Section: Discussionsupporting
confidence: 76%
“…10.1029/2023GC010867 2 of 26 Cesca et al, 2022;Farrell et al, 2009;Legrand et al, 2002;Lu et al, 2000;Schmid et al, 2022), in regions with geothermal activity or degassing (e.g., Fischer et al, 2014;Mesimeri et al, 2021), but also on tectonic faults (e.g., Passarelli et al, 2018), at plate boundaries (e.g., Vidale & Shearer, 2006), in subduction zones (e.g., Holtkamp & Brudzinski, 2011;Valenzuela-Malebrán et al, 2021;Villegas-Lanza et al, 2016), and in various settings associated with slow slip events (Passarelli et al, 2021;Sirorattanakul et al, 2022).…”
mentioning
confidence: 99%
“…There have been accumulated reports on crustal deformations during earthquake swarms (Gualandi et al., 2017; Himematsu & Furuya, 2015; Jiang et al., 2022; Lohman & McGuire, 2007; Martínez‐Garzón et al., 2021; Ruhl et al., 2016; Sirorattanakul et al., 2022; Takada & Furuya, 2010; Wei et al., 2015; Wicks et al., 2011; Yukutake et al., 2022). Previous studies have reported cases where the contribution of aseismic slip in moment release is more than that of seismicity (Himematsu & Furuya, 2015; Lohman & McGuire, 2007; Nishimura et al., 2022; Wicks et al., 2011; Wei et al., 2015; Yukutake et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Garagash obtained an integral equation similar to (4.1) based on the non-singularity of shear stress rate at the locking front (eqn (19) in [39]). Such an integral equation is valid under the assumptions of his study in two-dimensional elasticity for a solitary steady pulse travelling in anti-plane (III) or in-plane (II) mode of sliding.…”
Section: Pulse-like Circular Rupturesmentioning
confidence: 99%
“…Moreover, a similar mechanism might be also operating behind some natural episodes of seismicity such as seismic swarms and aftershock sequences. In fact, both phenomena are commonly interpreted to be driven by either the diffusion of pore pressure [14,15] or the propagation of aseismic slip [16,17], with recent studies suggesting that both mechanisms might be indeed coupled and responsible for the observed spatio-temporal patterns of seismicity [18][19][20]. Likewise, tectonic tremors and low-frequency earthquakes are often considered to be driven by slow slip events in subduction zones [21,22], at depths where systematic evidence of over-pressurized fluids is found [22,23].…”
Section: Introductionmentioning
confidence: 99%